Treatment of Foreign Investments during Armed Conflicts: The Regimes. (18th December 2018) - Liubashenko, Viacheslav
Abstract: Despite a wide range of progressive developments in modern international law over last decades problems relative to investments circulation in time of an armed conflict are of urgent interest to the lawyers. Besides the fact that practice of treatment of investments by States in times of armed conflicts are still diversified, the existing legal framework do provide the terms for protection of foreign investments. While the provisions of international humanitarian law, obviously, are central in factual assessment, modern international investment treaties also contribute to the issue by encompassing special clauses—overall framework consists from provisions from different branches of international law. The article offers a comprehensive analysis of existing international law of treaties, international humanitarian law and international law on foreign investment in relation to treatment of foreign investments during armed conflicts. It explores correlation and collision of norms within mentioned areas of international law and applicability of legal principles (distinction between property of the belligerent and the nonbelligerent party is the primary one) to concrete situations of international and noninternational armed conflicts; through identification and interpretation of provisions relative to confiscation (expropriation) and compensation it goes to construction of the regimes of treatment of foreign investments during armed conflicts. The article concludes with separation of the regimes and the provisions including them.